Information science in theory and practice - Vickery, B. C. (Brian Campbell); Vickery, Alina; Gale Group (Munchen K.G. Saur, 2004)
"An introduction to the field of information science text that covers the most recent changes to affect the profession, including the Internet and its role in information science and librarianship. Of academic and professional interest."--GVRL description.
Information science: emergence and scope -- A social approach to information -- Wider contexts of information transfer -- People and information -- Information retrieval -- Semantics and retrieval -- Intermediaries and interfaces -- Information systems -- The evaluation of systems -- The internet and information science.
Electronic reproduction.
Keywords: Information science; Electronic books